Root responses of Quercus ilex L. seedlings to drought and fire - Chiatante, D; Di Iorio, A; Scippa, G S (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract Drought treatments in holm-oak (Quercus ilex) seedlings induce variations in total root length, number of root apices, shoot/root dry weight, and root electrolyte leakage. When drought treatments last for more than 50 days a considerable number of fine lateral roots die, irrespective of branching order or distribution within the root system. Scorching of drought-treated seedlings induces a transient stimulation of root growth. These results indicate that root turnover is deeply affected during treatments, with survival of seedlings being entrusted to the tolerance of a number of roots situated in the deeper region of the root system. Activity of the meristematic tissue present within the apices of these surviving roots supports regeneration of above-ground lost organs during recovery. Knowledge of the mechanisms ensuring the survival of Mediterranean tree seedlings following drought and fire is useful for developing models of vegetation dynamics.
doi: 10.1080/11263500500160591
Keywords: Drought; Quercus ilex; root system; seedlings; ﬁre